PERSEPSI TUKANG BATU DI DESA JENETALLASA TENTANG TAKDIR (ANALISIS TEOLOGIS) - Nabilah, Maryam; Indah, Astrid Veranita (Sulesana, 2024)
Destiny is not only understood as an absolute provision but has a dimension that involves wise planning and determination according to the will and knowledge of Allah SWT. First, with this understanding it provides a foundation for understanding how the concept of destiny in human life, both in theological and practical aspects. Second, the masons in Jenetallasa village understand destiny as a combination of human effort and God's will. They believe that although destiny is a definite provision, humans are still required to try. Destiny in the view of masons, teaches surrender, acceptance, and patience in facing life's challenges. Third, the application of destiny by masons in Jenetallasa village has various ways, namely including effort, prayer, and acceptance of destiny, with variations in the level of surrender and effort made by each individual according to their views on destiny. The implications of the research suggest that understanding destiny has a broad impact on the lives of individuals and society. Therefore, spiritual development that can deepen this understanding can be used as a strategic step to create a more productive, harmonious, and religious society. This type of research is qualitative with a field research approach, namely research conducted by going directly to the location to collect the required data. The author applies the observation method by observing directly and using interview techniques. Interviews are conducted through conversations between two parties, between the author and the informant.